“Right-Wing Safe Space” Versus “Comrade Major”: Media Ideologies of Far-Right Russian Social Media Users - Petr Oskolkov; Eyal Lewin; Sabina Lissitsa (Social Media + Society)
A significant part of far-right activities worldwide take place within the media ecosystem formed by accounts and communities on social media platforms. Drawing on the media ideology approach, this study investigates how far-right Russian internet users perceive various social media platforms and how their sociopolitical beliefs affect these perceptions. Based on a series of in-depth semi-structured interviews, we argue that far-right users assess social media platforms according to the criteria of security, meaning privacy and non-cooperation with law enforcement agencies; freedom from moderation; and functionality, including informational, communicational, recreational, and self-expressional roles. The results demonstrate that, for a sociopolitically stigmatized user cohort, media ideology becomes a tool for adaptation and survival, stressing the factors of privacy protection and ideological proximity.